2015
DOI: 10.1364/oe.23.029399
|View full text |Cite
|
Sign up to set email alerts
|

Design and demonstration of phase gratings for 2D single grating interferometer

Abstract: In this study, we examined five types of phase gratings in a two-dimensional (2D) single grating interferometer with multidot metal targets embedded in a diamond substrate. For a phase grating consisting of two stacked 1D π/2-phase gratings and a checkerboard π-phase grating the multidot-pattern self-images with high visibility (40%) were obtained as expected from simulations. In addition to an absorption image, differential phase contrast and dark-field images in both x and y directions were derived from a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…With further development, this work may open a new way to produce lowcost 2D self-assembled crystals for certain applications, such as opto-electric devices, 34 lithography templates, 35 and photonic materials. 36,37…”
Section: Discussionmentioning
confidence: 99%
“…With further development, this work may open a new way to produce lowcost 2D self-assembled crystals for certain applications, such as opto-electric devices, 34 lithography templates, 35 and photonic materials. 36,37…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the microstructured array anode target source is equivalent to a G0 grating with 90% absorption placed in front of an extended X-ray source. Morimoto et al have demonstrated that TLGI produces high visibility fringes using a MAAT source in an experiment that realized a compact interferometer without the need for any inefficient absorption grating (Morimoto et al 2014, Morimoto et al 2015b, Morimoto et al 2015a).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, it means one less grating and the related inefficacy, electro-mechanical components, alignment and stability issues. Furthermore, Inverse Talbot-Lau geometry (Donath et al 2009) or Lau effect geometry (Momose et al 2011) which requires small period G0 absorption grating (or MAAT) can be achieved (Morimoto et al 2014, Morimoto et al 2015a, Morimoto et al 2015b). Using this geometry removes the requirement for a G2 absorption grating which may be removed entirely, further simplifying the interferometer by reducing the optical components required to a single phase grating.…”
Section: Advantagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the X-ray community, the earlier implementations to achieve directional sensitivity were based either on rotating the interferometer setup or the sample 50,51 . Furthermore, different approaches including new grating designs, such as checkerboard and speckle patterns paved the way for further developments [52][53][54][55][56][57][58][59] . Among all the disparate grating geometries the circular design has been implemented to characterize the transverse coherence of Xray beams, demonstrating the advantages of this solution, and opened up the possibility for additional applications 60 .…”
mentioning
confidence: 99%